2016
DOI: 10.1002/mrm.26254
|View full text |Cite
|
Sign up to set email alerts
|

3D Cartesian MRI with compressed sensing and variable view sharing using complementary poisson‐disc sampling

Abstract: Purpose To enable robust high spatio-temporal-resolution 3D Cartesian MRI using a scheme incorporating a novel variable density random k-space sampling trajectory allowing flexible and retrospective selection of the temporal footprint with compressed sensing (CS). Methods A “complementary Poisson-disc” k-space sampling trajectory was designed to allow view sharing and varying combinations of reduced view sharing with CS from the same prospective acquisition. These schemes were used for two-point-Dixon-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 44 publications
0
35
0
Order By: Relevance
“…While reducing the effective acceleration to an overall modest 4‐fold acceleration (neglecting the temporal dimension), this pattern combined increased k‐space sampling, especially in the higher frequencies with sufficient incoherent sampling for a successful k‐t CS reconstruction, hence minimizing the spatial resolution loss as shown by the reduced blurring level. The success of this strategy is similar to the favorable results with view‐sharing to gain spatiotemporal resolution in 3D Cartesian MRI (e.g., for dynamic contrast‐enhanced applications) . Blinded radiologist assessment showed that perfusion‐weighted volumes acquired with this sampling strategy led to diagnostically acceptable images, especially in terms of cortico‐medullary contrast and low artifacts level compared to single‐averaged CS accelerated data.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…While reducing the effective acceleration to an overall modest 4‐fold acceleration (neglecting the temporal dimension), this pattern combined increased k‐space sampling, especially in the higher frequencies with sufficient incoherent sampling for a successful k‐t CS reconstruction, hence minimizing the spatial resolution loss as shown by the reduced blurring level. The success of this strategy is similar to the favorable results with view‐sharing to gain spatiotemporal resolution in 3D Cartesian MRI (e.g., for dynamic contrast‐enhanced applications) . Blinded radiologist assessment showed that perfusion‐weighted volumes acquired with this sampling strategy led to diagnostically acceptable images, especially in terms of cortico‐medullary contrast and low artifacts level compared to single‐averaged CS accelerated data.…”
Section: Discussionmentioning
confidence: 59%
“…The success of this strategy is similar to the favorable results with view-sharing to gain spatiotemporal resolution in 3D Cartesian MRI (e.g., for dynamic contrast-enhanced applications). 41 Blinded radiologist assessment showed that perfusion-weighted volumes acquired with this sampling strategy led to diagnostically acceptable images, especially in terms of cortico-medullary contrast and low artifacts level compared to single-averaged CS accelerated data. A similar evaluation should be performed in clinical cases to fully assess the clinical applicability of this sequence.…”
Section: Discussionmentioning
confidence: 93%
“…First, investigations have sought the best undersampling scheme, which should be as random as possible to create incoherent undersampling artefacts so that a proper nonlinear reconstruction can be applied to suppress noise-like artefacts without degrading image quality of the reconstruction [12], [13], [14]. The sparsity of the random undersampling determines the acceleration rate.…”
Section: Related Work and Our Contributions A Classic Model-basementioning
confidence: 99%
“…Our results show preliminary experience with an ultrafast volumetric bilateral breast MRI exam with submillimeter isotropic resolution, surpassing the clinical standard while providing temporal resolutions 6‐to‐15‐fold faster than typical clinical protocols. Although a judicious combination of CS and view sharing can produce high spatiotemporal resolution in various DCE MRI applications, the imaging performance of these methods is object dependent . The local spatially variant temporal constraint is able to further exploit data redundancy by learning and modeling temporal behavior rather than the assumption of consistency over a period of time .…”
Section: Discussionmentioning
confidence: 99%